Effect of different types of graphene coatings on friction and wear performance of aluminum alloy. Issue 4 (7th February 2022) - Mura, Andrea; Canavese, Giancarlo; Goti, Edoardo; Rivolo, Paola; Wang, Haozhe; Ji, Xiang; Kong, Jing
Abstract: In this work graphene coatings have been deposited on aluminum alloy samples to investigate whether they can improve wear strength and promote friction reduction, which means components reliability and efficiency. Tribological performance has been tested by pin-on-disk wear tests. Three procedures to coat the samples have been explored. One is based on transferred graphene method and the other two are based on percolative graphene. Results show that graphene coatings last little time onto the sample surface, though strongly reducing the coefficient of friction of aluminum samples as far as they endure.